Pengaturan Hukum Internasional Terhadap Limbah Makanan dan Dinamikanya di Indonesia - Zuhra, Amalia; Angkasari, Wildani (Faculty of Law, Universitas Jambi, 2023)
The problem of food waste has become one of the increasingly concerning environmental issues in Indonesia. Improperly managed food waste, such as air, water, and soil pollution, can negatively impact the environment. This article aims to discuss the impacts of food waste on the environment, international legal regulations related to the issue, and the latest developments in Indonesia in addressing food waste. The research method used in this study is a literature review using scientific journals, books, and related documents. The results show that food waste can cause severe environmental damage and needs to be addressed seriously. Countries have adopted several international legal rules to address the problem of food waste, such as the Basel Convention and the Stockholm Declaration. In Indonesia, efforts to address food waste have been made, such as by promoting food waste reduction through education campaigns and waste recycling programs. However, more significant and integrated efforts are needed from the government, society, and private sector to address the problem of food waste effectively. In conclusion, this article emphasizes the need for coordinated and comprehensive action to address the increasingly concerning problem of food waste at the local and global levels. Keywords: international law; food waste; environment